Subcellular localization of class II HDAs in Arabidopsis thaliana: nucleocytoplasmic shuttling of HDA15 is driven by light. - Malona V Alinsug (Public Library of Science (PLoS), 2012)
Class II histone deacetylases in humans and other model organisms undergo nucleocytoplasmic shuttling. This unique functional regulatory mechanism has been well elucidated in eukaryotic organisms except in plant systems. In this study, we have paved the baseline evidence for the cytoplasmic and nuclear localization of Class II HDAs as well as their mRNA expression patterns. RT-PCR analysis on the different vegetative parts and developmental stages reveal that Class II HDAs are ubiquitously expressed in all tissues with minimal developmental specificity. Moreover, stable and transient expression assays using HDA-YFP/GFP fusion constructs indicate cytoplasmic localization of HDA5, HDA8, and HDA14 further suggesting their potential for nuclear transport and deacetylating organellar and cytoplasmic proteins. Organelle markers and stains confirm HDA14 to abound in the mitochondria and chloroplasts while HDA5 localizes in the ER. HDA15, on the other hand, shuttles in and out of the nucleus upon light exposure. In the absence of light, it is exported out of the nucleus where further re-exposition to light treatments signals its nuclear import. Unlike HDA5 which binds with 14-3-3 proteins, HDA15 fails to interact with these chaperones. Instead, HDA15 relies on its own nuclear localization and export signals to navigate its subcellular compartmentalization classifying it as a Class IIb HDA. Our study indicates that nucleocytoplasmic shuttling is indeed a hallmark for all eukaryotic Class II histone deacetylases.